Analysis of Adolescent Creative Thinking Skills Scale Based on Creative Personality Perspective - Anne Hafina; Qawiyyan Fitri (Universitas Pendidikan Indonesia (UPI), 2022)
The continuous development of the world demands skill abilities in its human resources both in educational, economic, and artistic jurisdictions. Creative thinking skills are one of the important skills to have and develop to survive and compete in the 21st century. Creative thinking skills are known as the ability to understand gaps or obstacles in life, the ability to adapt creatively, and the ability to solve problems creatively needed in the 21st century. The purpose of this paper is to develop a tool for assessing youth's creative thinking skills which are used to measure the creative attitudes of high school-aged youth. Based on the analysis of the relevant literature, this study developed 48 items that were intended to reflect the creative thinking skills of adolescents based on a creative personality perspective. The samples taken were 135 adolescents aged 15-20 years in the city of Bandung. Item validity and scale reliability were measured using the Rasch modeling. The results showed that 1) the Cronbach Alpha score was 0.88 in the very good category, 2) the item reliability coefficient was 1.00 in the special category, and 3) the person reliability coefficient was 0.87 in the good category, which means that adolescents respond consistently to each item. Based on the results of the Rasch modeling analysis, this paper maintains 46 valid items while 2 other items are invalid.